Gender, labor migration and changes in small-scale farming on Vietnam's north-central coast - Kawarazuka, Nozomi; Duong, T.M.; Simelton, Elisabeth (Informa UK Limited, 2020)
Drawing on the narratives of women and men who have domestic or international migration experiences, this study explores the gendered impacts of migration on small-scale farming in rural Ha Tinh province in Vietnam. The paper investigates men’s and women’s migration experiences, their influence on agricultural production, and impact on their livelihoods after migration. The findings show that households use various strategies to sustain agricultural production in the absence of some members. Women’s increased economic independence through labor migration has not necessarily lead to their increased management roles in agriculture, but they are increasingly challenging stereotypical images of rural women. While migration can be a catalyst for men to transform their livelihoods, it can also widen gaps in social and economic statuses among men.